Composition of public investment and economic growth: evidence from Turkish provinces, 1975-2001 - Gökçen Yilmaz (Public Sector Economics, 2018)

(untitled)
The relationship between public expenditure and economic growth is one of the central topics in economics literature, and an extensive body of knowledge has accumulated around it. The current consensus is that infrastructure, education and health are the types of public services that are likely to contribute to economic growth. Still, the question of how public resources should be allocated among them remains unanswered. This paper, benefiting from an endogenous growth model that is useful in the identification of the optimal allocation of public resources, analyses the growth effect of the composition of public investment in Turkey using a dataset for the years between 1975 and 2001. Results indicate that, between these years, the government overinvested in transportation and communication services and underinvested in energy infrastructure, education, health, and city infrastructure and security services. There is further evidence that public policy led to an underinvestment in energy infrastructure in these years. The scope of the analysis is confined by the limitations of the economic model. Additionally, the robustness of the results depends on the assumption that public policy is exogenous in the model.